Analisis Butir Soal Ujian Tengah Semester Ganjil Mata Pelajaran Seni Budaya Kelas VII Di SMPN 5 Padang 2019/2020 - Anggun Septiani Queenta; Yuliasma Yuliasma (FBS Universitas Negeri Padang, 2020)
This study aims to determine the quality of question item of the Odd Mid-term Examination for Art and Culture subject in grade 7 of SMPN 5 Padang in Academic Year 2019/2020 in terms of validity, reliability, difficulty level, discriminating power and effectiveness of deceivers. This research is a quantitative descriptive research. The subjects in this study were all students (254 students) in grade 7. The object in this study was the question items of mid-term Exam, key answers, and participants' answers. The data were collected through documentation and interview. The data analysis was conducted by using the ANATES program version 4.0.9. The results of this study indicate that: (1) Based on validity, there are 45 valid questions (90%) and 5 invalid questions (10%). (2) Based on reliability, the items have high reliability which is 0.78. (3) Based on the level of difficulty, there are 6 difficult items (12%), 31 medium items (62%), and 13 easy items (26%). (4) Based on discriminating power, there is 1 question categorized as a bad item (2%), 10 question categorized as pretty good items (20%), 23 question categorized as good items (46%), and 16 question categorized as very good items (32%). (5) Based on the effectiveness of the deception/distractor, there are 28 items functioning very well (36%), 17 items functioning well (34%), 4 items functioning quite well (8%), and 1 item functioning poorly (2% ). (6) Based on the quality of the questions, there are 27 items which are good in quality (54%), 15 items which are less good (30%), and 8 items which are not good (16%).